EXPERIENCES, PERCEPTIONS, AND RECOMMENDATIONS FOR FACULTY DEVELOPMENT PROGRAMS IN HEALTH PROFESSIONS EDUCATION: A QUALITATIVE STUDY - Khan, Muhammad Junaid; Sethi, Ahsan; Khan, Sana; Lajber, Mehreen; Hayat, Zubia; Asim, Nowshad (Journal of Ayub Medical College Abbottabad, 2024)
Background: Faculty development programs (FDPs) in health profession education (HPE) impact teaching in different ways. There has been limited literature on the impact of such programs in developing countries. This qualitative study explores the experiences, perceptions, and recommendations of faculty attending these FDPs. Methods: A qualitative case study involving purposively selected public and private medical college faculty members were enrolled. Semi-structured interviews were conducted with 14 faculty members across the country. Thematic analysis was done using ATLAS. Results: The study revealed three main themes. The first, "experiences with FDPs," has three subthemes, i.e., faculty limited engagement, key areas of FDPs and the need for interactivity and collaboration. The second theme is based on "participants’ perception", with two subthemes: key indicators and how teaching skills are improved and some challenges versus recommendation, as the third theme emerged from the data analysis. Conclusion: In the current context, FDPs, as experienced by medical professionals, emphasise the need for administrative facilitation, tailored and technology-driven flexible programs that foster faculty exposure, interactivity, and collaboration. The perceptions ensued in using innovative strategies within the FDPs with feedback and evaluation. However, recommendations target the national accreditation bodies or institutions and individual schools to devise training centres as per needs assessment. Future studies should develop and validate a tool based on key indicators for the proper evolution of the effectiveness of FDPs.